The comparative effectiveness of distributed and colocated team after-action reviews. Issue 5 (19th October 2016) - Jarrett, Steven M.; Glaze, Ryan M.; Schurig, Ira; Muñoz, Gonzalo J.; Naber, Andrew M.; McDonald, Jennifer N.; Bennett, Winston; Arthur, Winfred
ABSTRACT: Despite their frequent use in the military and private sectors, the comparative effectiveness of colocated and distributed after-action reviews (AARs) is relatively unknown. Consequently, this study examined the comparative effectiveness of colocated and distributed AARs across taskwork and teamwork outcomes. Data were obtained from 492 participants randomly assigned to 123 four-person teams who participated in one of six AAR conditions. The results indicated that teams in the AAR conditions had significantly higher performance and team efficacy scores than the teams in the non-AAR conditions. In summary, the findings highlight that regardless of the training environment or type of AAR, the AAR remains an effective method at increasing performance and other outcomes. Therefore, the use of distributed AARs does not engender the posited process losses that were hypothesized.